1995
DOI: 10.1093/oxfordjournals.humrep.a135896
|View full text |Cite
|
Sign up to set email alerts
|

Blastocyst development and birth after in-vitro maturation of human primary oocytes, intracytoplasmic sperm injection and assisted hatching

Abstract: Immature oocyte recovery followed by in-vitro oocyte maturation and in-vitro fertilization is a promising new technology for the treatment of human infertility. The technology is attractive to potential oocyte donors and infertile couples because of its reduced treatment intervention. Immature oocytes were recovered by ultrasound-guided transvaginal follicular aspiration. Oocytes were matured in vitro for 36-48 h followed by intracytoplasmic sperm injection (ICSI). Embryos were cultured in vitro for 3 or 5 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(82 citation statements)
references
References 0 publications
1
78
0
3
Order By: Relevance
“…The administration of testosterone propionate had a virilizing effect on the external genitalia of female lambs as described previously (Barnes et al 1995, Unsworth et al 2005. Testosterone-treated lambs had genitalia that were very similar to males, with a penis and scrotal tissue, but with no testicular tissue.…”
Section: Effect Of Prenatal Androgen Exposure On External Appearance mentioning
confidence: 54%
“…The administration of testosterone propionate had a virilizing effect on the external genitalia of female lambs as described previously (Barnes et al 1995, Unsworth et al 2005. Testosterone-treated lambs had genitalia that were very similar to males, with a penis and scrotal tissue, but with no testicular tissue.…”
Section: Effect Of Prenatal Androgen Exposure On External Appearance mentioning
confidence: 54%
“…A plausible reason for the hampered development of NT embryos may be that the remodelling of foreign nuclei into an active zygotic genome is not totally successful. When suitable media are used, parthenogenetic embryos maintain their own gametogenetic content and can develop until the blastocyst stage (Barnes et al, 1995;Bavister, 1995). Kishikawa et al (1999) reported rates of morula/blastocyst formation of 58% for mouse NT embryos versus 98% for parthenogenetic control embryos.…”
Section: Discussionmentioning
confidence: 99%
“…The KSOM medium (Erbach et al, 1994) was prepared in the laboratory; it had a low glucose content (0.2 mM) and was supplemented with 4 mg/mL BSA. The G1 and G2 media (Barnes et al, 1995) were commercially obtained (Scandinavian IVF, Gotheburg, Sweden). KSOM, as well as G1 and G2, had an osmolarity of 265 mOsm.…”
Section: Mediamentioning
confidence: 99%
“…Only a few reports have been published for IVM of human oocytes from nonstimulated cycles in women, leading to term development (9,17,60,78,90). Oocyte viability and embryonic development after IVM are substantially lower than with VVM.…”
mentioning
confidence: 99%